Synbiotic aerated dessert: diet product development and evaluation of the intake effects in individuals with metabolic syndrome - Santos, Douglas Xavier dos (2017)
The objective of this work was to adapt a synbiotic aerated diet dessert, produced with the addition of a probiotic culture of Lactobacillus acidophilus La-5 and prebiotic ingredients (fructooligosaccharides and inulin), from the previously developed sucrose-containing formulation, and to evaluate the effects of its ingestion on adult volunteers with metabolic syndrome (MetS) during a period of 8 weeks of intervention. In addition, to improve the resistance of the probiotic to simulated gastrointestinal conditions, a microencapsulation process was optimized. For the development of the product, the formulations were produced in triplicates, in which probiotic culture survival, instrumental texture and sensory acceptability were evaluated up to 112 days of storage under freezing (-18 °C). Subsequently, a randomized, double-blind, placebo-controlled trial was carried out in which the product developed was administered to forty-five volunteers with MetS assigned into two groups, each receiving 40 g/day of: synbiotic diet mousse (SDM) (n=23) and placebo diet mousse (PDM) without pro- and prebiotics (n=22). Fasting blood samples were collected at the beginning and after 8 weeks of daily consumption of both mousses to determine the anthropometric, biochemical, haematological, inflammatory, and immunological parameters. Afterward, with the goal of improving the survival of L. acidophilus La-5 to in vitro simulated gastrointestinal conditions, the microencapsulation process conditions of the probiotic strain via spray drying were optimized using inulin as the encapsulating agent. The viability of L. acidophilus La-5 incorporated into SDM was above 7.8 log CFU/g and remained stable throughout storage. PDM showed lower acceptability (5.77-6.50) after storage than SDM (6.67-7.03). The texture was the most appreciated attribute and hardness of the SDM increased during storage, but remained stable for PDM. The clinical trial revealed significant reductions of total cholesterol and HDL-cholesterol, as well as of immunoglobulins (A and M), and interleukin-1β in both groups during the intervention period. However, regarding intergroup changes, there were not any significant differences for all parameters evaluated (p>0.05). After the optimization of the microencapsulation process of the probiotic culture (80 mL/min, 82% and 10%, respectively for feed flow, aspiration rate, and inulin concentration), the microencapsulated probiotic strain incorporated in the SDM mousse showed the highest in vitro gastrointestinal survival (p<0.05) in the different stages of the assay, as follows: after the gastric phase: 5.68 log CFU/g (83.3%), the enteral phase I: 5.61 log CFU/g (82.3%), the enteral phase II: 5.56 log CFU/g (81.4%). Therefore, these results suggest that the presence of probiotic and prebiotics in SDM did not provide an additional effect on the health of volunteers with MetS. Additionally, the results confirm the appropriateness of the spray drying process to microencapsulate L. acidophilus La-5 using inulin as coating agent, providing increased resistance to the microencapsulated probiotic strain under in vitro gastrointestinal stress.